Evaluación de las tendencias de la contaminación del recurso hídrico de la parte alta de la microcuenca del río Cutuchi, en la provincia de Cotopaxi, periodo 2019-2020. - Rojas Benavides, Carla Yessenia (2020)
The pollution of rivers is a very common problem nowadays, being necessary tools that allow to determine the degree of pollution in a river. This research aims to evaluate the water quality in the high part of the Cutuchi River micro-watershed using the Canadian Council of Ministers of the Environment (CCME) and National Sanitization Foundation (NSF) methods. Thus, such as the application of the variance analysis through the completely randomized design and means comparison tests (Tukey). The analysis of water quality trends was also carried out using the Spearman`s Rho non-parametric test for a monthly period from 2010 to 2011. Seven evaluation points were established, distributed along the upper part of the micro-watershed. The results allowed identifying that the parameters BOD5 (24.47 mg/l), dissolved oxygen (19.9%) and fecal coliforms (1507.93 NMP) are out of the maximum permissible limits established in the TULSMA. According to the ICA-CCME and ICA-NSF methods, the point with the best water quality is located in the Cutuchi river, Quebrada San Rafael, San Ramón sector, for the period 2010 to 2011, determining a medium to good quality. The trend analysis identified the Cutuchi River, Ex-Navisco sector, as a point that presented an improvement in water quality ranging from bad to medium (p<0.01).